(untitled) (Educação e Pesquisa, 2020)
The present work discusses the possible correspondence between the production of knowledge in the scope of programs of graduation in Education and their contribution for the improvement of Basic Education in Brazil, through the stimulation to research made by promotion agencies, particularly the CNPq – through the Productivity in Research Scholarship (PQ). It also aimed to compare the process of granting support to individual projects in Brazil and possible symmetries with projects supported by the European Union. All these actions aim to demonstrate how the area of Education has positioned itself in the context of Brazil’s scientific production, in terms of absolute numbers and thematic categorization, and how all these factors can influence, or already do, in the process of improving Basic Education. The data was collected from CNPq’s C&T Investments’ site, from Lattes Platform and from CAPES’ evaluation. After collecting the data it was made a categorization of the projects. Among the results can be observed a concentration of those who receive PQ Scholarships, and also the PQ scholarship holders’ scientific production, in the regions Southeast and South. Regarding the initial attempt to categorize CNPq’s research projects in the area of education relating them to the PQ Scholarships, it was observed a great valorization of themes that continue the conceptual aspects of dissertations and thesis of their researchers and the orientations that conduct them. In the context of Basic Education, there was great thematic coverage of subjects that range from teaching to international comparisons.